Differences in innate immune signaling between alcoholic and non‐alcoholic steatohepatitis. (15th July 2013) - Petrasek, Jan; Csak, Timea; Ganz, Michal; Szabo, Gyongyi
Abstract: The similar histopathological characteristics of alcoholic steatohepatitis (ASH) and non‐alcoholic steatohepatitis (NASH), and the crucial role of the innate immune response in both conditions may lead to the assumption that ASH and NASH represent the same pathophysiological entities caused by different risk factors. In this review paper, we elaborate on the pathophysiological differences between these two entities and highlight the disease‐specific involvement of signaling molecules downstream of the Toll‐like receptor 4, and the differential mechanism by which the inflammasome contributes to ASH versus NASH. Our findings emphasize that ASH and NASH have disease‐specific mechanisms and therefore represent distinct biological entities. Further studies are needed to dissect the emerging differences in pathogenesis of these two conditions.